THE GENERAL STATE OF WATER RESOURCES IN MONTENEGRO - Sekulić, Goran; Ćipranić, Ivana; Ostojić, Milena; Ćalasan, Olga (Journal of Applied Engineering Science, 2024)
Water resources are essential for the functioning of societies and ecosystems, affecting public health, food production, industry and overall environmental stability. A country’s ability to manage and maintain its water resources is closely related to economic prosperity, social well-being and ecological health. The paper shows Montenegro’s current state of water resources, highlighting negative trends and challenges. It focuses on three significant issues: difficulties securing sufficient water quantities, escalating problems related to water protection from floods, and growing threats to humans and the environment due to water pollution and ecosystem destruction. Global climate change exacerbates these challenges, affecting rainfall patterns and leading to destructive water waves. Despite the apparent abundance, the irregular distribution of water resources poses a significant problem, particularly in the Dinaric karst area. The paper discusses limitations in water resource management, emphasising the challenges posed by spatial, ecological, urban, and sociological factors. It also addresses the untapped hydro energy potential in Montenegro, highlighting the country’s dependence on electricity imports despite having the capability to generate a substantial portion through hydro energy. The general conclusion emphasises the need for a comprehensive and sustainable approach to solving the complex challenges facing water resources in Montenegro. Finally, the paper calls for increased international cooperation in developing and implementing effective policies for the sustainable use and preservation of water resources as one of the most critical resources of a country.